Detection of extra-regional tumour recurrence with 18F-FDG-PET/CT in patients with recurrent gynaecological malignancies being considered for radical salvage surgery. Issue 4 (April 2017) - Brar, H.; May, T.; Tau, N.; Langer, D.; MacCrostie, P.; Han, K.; Metser, U.
Abstract : Aim: To compare the detection rate of extra-regional metastases in patients with recurrent gynaecological malignancies being considered for radical salvage surgery with combined 2-[ 18 F]-fluoro-2-deoxy-d- glucose ( 18 F-FDG) positron-emission tomography (PET)/computed tomography (CT) compared to conventional imaging. Materials and methods: A retrospective review was performed of all patients in a provincial database with recurrent gynaecological malignancies being considered for pelvic exenteration that underwent restaging with CT/PET between March 2011 and October 2014. Findings on PET and conventional imaging (CT ± pelvic MRI) were abstracted. Disease sites were classified according to the location (regional nodal metastases, extra-regional nodal metastases, peritoneum, or other distant sites) and diagnostic certainty (definitive or equivocal). The proportion of patients positive for extra-regional recurrence was calculated for PET and conventional imaging. In addition, the proportion of patients with indeterminate lesions only was calculated for each modality and the sites of indeterminate findings were tabulated. Results: There were 85 patients (median age, 50 years; range: 30–81 years) with carcinoma of cervix ( n =51), endometrium ( n =18), vagina ( n =6), or vulva ( n =10). Extra-regional recurrence was detected in 8/85 (9.4%) and 24/85 (28.2%) patients on conventional imaging and PET, respectively ( p =0.0017). The greatest impact of PET compared to conventional imaging was in the detection of extra-regional nodal metastases. PET had significantly fewer examinations equivocal for extra-regional recurrence versus conventional imaging (6/85 [7.1%] and 38/85 [44.7%], respectively, p <0.001). Conclusion: In patients with recurrent gynaecological malignancies being considered for radical salvage surgery, PET may identify significantly more extra-regional recurrence than conventional imaging. PET may also result in fewer equivocal lesions. The impact of these results on patient management and outcome should be confirmed in future prospective trials. Highlights: For a small proportion of patients with recurrent gynecological malignancy, radical salvage surgery can be a successful treatment option. Appropriate patient selection and exclusion of extra-regional metastases is paramount. PET may identify more extra-regional recurrences than conventional imaging, facilitating patient selection for surgical salvage.